Value proposition and the impact of tourism: A study in the Las Pampas town center of Tomayquichua-Huánuco, Perú - Martel-Zevallos, David J. (2019)
The objective of the research was to demonstrate how the value proposition is related to the impact of tourism in the Las Pampas de Tomayquichua town center, based on applied research, with a quantitative approach, descriptive-correlational-explanatory scope and type experimental. For the application of the questionnaire to the population, a simple random sample of probabilistic type was taken, reaching 295 and for the experimental group a simple random sub sample of an intentional non-probabilistic type was taken, bequeathing 15 inhabitants. From the results we obtained that 38.64% said that the reason for visiting The Pampas would be for their tourist areas, followed by 34.92% indicating that it is for their chapels, while 22.37% said for the healthy climate, and only one 4.07% indicated that it is for recreation and recreation. Reaching the conclusion that the value proposal is related to the impact of tourism in the town of Las Pampas de Tomayquichua with a correlation of 0.70665582, so it is a positive relationship as it approaches the value of 1.